Ceramide-Induced Lysosomal Biogenesis and Exocytosis in Early-Onset Preeclampsia Promotes Exosomal Release of SMPD1 Causing Endothelial Dysfunction - Ermini, Leonardo; Farrell, Abby; Alahari, Sruthi; Ausman, Jonathan; Park, Chanho; Sallais, Julien; Melland-Smith, Megan; Porter, Tyler; Edson, Michael; Nevo, Ori; Litvack, Michael; Post, Martin; et al. (Frontiers in Cell and Developmental Biology, 2021)
Aberrant ceramide build-up in preeclampsia, a serious disorder of pregnancy, causes exuberant autophagy-mediated trophoblast cell death. The significance of ceramide accumulation for lysosomal biogenesis in preeclampsia is unknown. Here we report that lysosome formation is markedly increased in trophoblast cells of early-onset preeclamptic placentae, in particular in syncytiotrophoblasts. This is accompanied by augmented levels of transcription factor EB (TFEB). In vitro and in vivo experiments demonstrate that ceramide increases TFEB expression and nuclear translocation and induces lysosomal formation and exocytosis. Further, we show that TFEB directly regulates the expression of lysosomal sphingomyelin phosphodiesterase (L-SMPD1) that degrades sphingomyelin to ceramide. In early-onset preeclampsia, ceramide-induced lysosomal exocytosis carries L-SMPD1 to the apical membrane of the syncytial epithelium, resulting in ceramide accumulation in lipid rafts and release of active L-SMPD1 via ceramide-enriched exosomes into the maternal circulation. The SMPD1-containing exosomes promote endothelial activation and impair endothelial tubule formation in vitro. Both exosome-induced processes are attenuated by SMPD1 inhibitors. These findings suggest that ceramide-induced lysosomal biogenesis and exocytosis in preeclamptic placentae contributes to maternal endothelial dysfunction, characteristic of this pathology.